Simultaneous determination and pharmacokinetic study of three isoflavones from Trifolium pratense extract in rat plasma by LC‐MS/MS. (5th June 2014) - Zhang, Rui; Wang, Shouyu; Lu, Ming; Zhang, Zhen; Tian, Xiliang; Lv, Decheng
Abstract A highly selective and sensitive liquid chromatography–tandem mass spectrometry has been developed and validated for simultaneous determination of three isoflavones – ononin, formononetin and biochanin A – in rat plasma using lysionotin as internal standard (IS). The plasma samples were pretreated and extracted by liquid–liquid extraction. Chromatographic separation was accomplished on a C18 column with the column temperature of 30 °C and a mobile phase of methanol–0.1% formic acid (75:25, v/v). The detection was accomplished by multiple‐reaction monitoring scanning with positive/negative ion‐switching electrospray ionization mode. The optimized mass transition ion pairs (m/z) for quantitation were 431.3/269.1 for ononin, 267.1/252.2 for formononetin, 283.2/268.2 for biochanin A and 343.2/313.3 for IS. The total run time was 8.0 min. Full validation of the assay was implemented, including selectivity, sensitivity, linearity, precision, accuracy, recovery, matrix effect and stability. This is the first report on simultaneous determination of the three major isoflavones in rat plasma after intragastric administration of Trifolium pratense extract. The results provided a significant basis for the clinical application of this herb Trifolium pratense. Copyright © 2014 John Wiley & Sons, Ltd.